Factors Associated with Low Back Pain among Nurses at Tertiary Level Hospital in Kathmandu - Thapaliya, Subekshya; Mishra, Ravi K; Subedi, Krishna K (Journal of Institute of Medicine Nepal, 2022)
Introduction: Nursing is a profession with high incidence and prevalence of low back pain with its medical and professional consequences. Personal and work-related factors are regarded as causal factors for back pain. The aim of study was to find out the Prevalence and contributing factors of low back pain among nurses working at a Tertiary level Hospital in Kathmandu. Methods: A cross-sectional study was conducted among 290 nurses from different units/wards at Tribhuvan University Teaching Hospital. A self-administered, modified Nordic questionnaire and Keele Start Back Screening were used to collect data regarding prevalence of low back pain, its risk status and contributing factors. Descriptive statistics, inferential and univariate and multivariate logistic regression techniques were used for analysis. Results: The findings of this study broadly confirm the high levels of back pain in nursing, with a one-year prevalence of low back pain of 84.1% for low back pain of at least one day and 21.92% among them were at high risk status. More than half (63.11%) of nurses reported from being prevented of carrying out normal activities. There was a significant association between low back pain and Age; 51-60 yrs (p= 0.04), body mass index; over weight (p = 0.03) and place of work; critical care unit (p = 0.02). Conclusion: The prevalence of low back pain among nurses was high and should be actively addressed.